Kajian Hukum Atas Pembantuan dalam Melakukan Penganiyaan dengan Rencana yang Mengakibatkan Kematian (Studi Putusan No. 212/Pid.B/2017/PN Gpr) - Julianto, Riki; Arifin, Ridwan (Faculty of Law, Universitas Jambi, 2024)
This article study the case of the District Court decision in the city of Kediri number 212/Pid.B/2017/PN Gpr in the same case as decision number 213/Pid.B/2017/PN Gpr, in which in both decisions there are many criminal elements that could be discussed such as complicity, forms of complicity within complicity, failure of assistance, reasons for reduce the sentences, and separation in filing criminal cases. the first decision was about assisting the crime and the second was about participating in the murder. Even though the two case files were split (splitsing), the material or subject matter was the same, predominantly about murder which was caused by rape to the defendant in prior. Both decisions are criminal acts of deelneming (complicity), complicity is a form of crime committed by more than one person who is involved psychologically or physically, so that the criminal responsibility of each person is different. The purpose of writing this article is to analyze a. whether and the criminal categorization of the perpetrator's actions in decision number 212/pid.B/2017/PN Gpr is coherent according to the teachings of criminal law regarding complicity (deelneming) b. whether assistance in the case of PN decision number 212/pid.B/2017/PN Gpr is failed-assistance of committing crime c. whether the court's decision in sentencing already adhere principle of reducing sentence. this research is using the normative-empirical legal research method with the approach of studying the judge's decision in the case of a criminal act that occurred. Abstrak Artikel ini merupakan kajian atas studi kasus putusan Pengadilan Negeri di kota Kediri no. 212/Pid.B/2017/PN Gpr dalam perkara yang sama dengan putusan no. 213/Pid.B/2017/PN Gpr, yang mana dalam kedua putusan tersebut banyak unsur pidana yang dapat dibahas seperti penyertaan, bentuk penyertaan dalam penyertaan, gagalnya penyertaan, alasan peringanan pidana, dan splitsing dalam pemberkasan kasus pidana. putusan pertama adalah tentang pembantuan tindak pidana dan yang kedua adalah tentang ikut serta dalam pembunuhan. Meski kedua berkas perkara dipisahkan (splitsing) tapi materi atau pokok perkaranya sama tentang sebuah tindak pidana pembunuhan yang disebabkan terlebih dahulu oleh pemerkosaan terhadap terdakwa pembantuan. Kedua putusan tersebut merupakan perkara tindak pidana deelneming (penyertaan), dimana tindak pidana dilakukan oleh lebih dari satu orang yang terlibat secara psikis atapun fisik sehingga tanggung jawab pidana masing-masing berbeda. Tujuan ditulisnya artikel ini adalah untuk menganalisis a. apakah pengkategorian pidana terhadap perbuatan pelaku dalam putusan no. 212/pid.B/2017/PN Gpr sudah tepat sesuai dengan ajaran hukum pidana tentang penyertaan (deelneming) b. apakah pembantuan dalam perkara putusan PN no. 212/pid.B/2017/PN Gpr merupakan pembantuan gagal terhadap tindak pidana c. apakah keputusan pengadilan sudah tepat dengan memperhatikan hal yang meringankan pidana. kasus Penelitian ini menggunakan metode penelitian hukum normatif-empiris dengan pendekatan kajian putusan hakim dalam kasus tindak pidana yang terjadi.